Self-care knowledge and activities of people with diabetes mellitus submitted to telephone support - Jéssica Magalhães Felipe Batista; Carla Regina de Souza Teixeira; Tânia Alves Canata Becker; Maria Lúcia Zanetti; Plínio Tadeu Istilli; Ana Emília Pace (Universidade Federal de Goias, 2017)
A quasi-experimental study that analyzed diabetes knowledge and self-care activities of people with diabetes mellitus and, their relationships with sociodemographic variables and glucose control after participating in a telephone support program. Forty-eight people constituted the sample, and they were interviewed using the tools Diabetes Knowledge Questionnaire and the Brazilian version of the Summary of Diabetes Self-Care Activities Questionnaire. We used descriptive analysis, with the Chi-Square and Fisher's Exact tests. We verified good knowledge before and after the intervention and, the relationship of this variable with the glycated hemoglobin post-intervention. Self-care activities presenting higher means were eating, glucose monitoring, feet care and, use of medications. The findings can be useful for educational interventions, and telephonic support has been shown as a tool that can help health teams in the attention to the person with diabetes mellitus.